POTENTIAL EFFECT OF MACRO ALGA Caulerpa sp. AND Gracilaria sp. EXTRACT LOWERING MALONDIALDEHYDE LEVEL OF WISTAR RATS FED HIGH CHOLESTEROL DIET - Julyasih, Ketut Srie Marhaeni; Wirawan, I Gede Putu (International Journal of Biosciences and Biotechnology; Vol 5 No 1 (2017)DO - 10.24843/IJBB.2017.v05.i01.p06, 2017)
Seaweed has potential nutrient content such as carotenoids, vitamins, fatty acids, carbohydrates, minerals, and other essential substances. Carotenoids have important biological functions as an antioxidant, and immunostimulatory which can prevent the disease, anti-inflammatory, anti-stress, anti-aging, and protect the skin from the harmful effects of ultraviolet radiation. Seaweed generally consumed as a vegetable by people in Bali, known as the local name Bulung Boni (Caulerpa spp.) and Bulung Sangu (Gracilaria spp.).. So far there has been no report or results of research on the effects of extract ethanol of Bulung Boni (Caulerpa sp.) and Bulung Sangu (Gracilaria sp.) as an antioxidant that can prevent lipid peroxidation which can be seen in decreased level of MDA in liver tissue or blood plasma. Therefore it is necessary to determine of plasmaMDA level of Wistar rat after fed high cholesterol diet treated with extract ethanol of Caulerpa sp. and Gracillaria sp. This experimental study used completely randomized design. Research using total of 24 Wistar rats divided into six sample groups of equal size, all fed with a diet high in cholesterol especially in negative control. The study consisted of negative control group (standard diet), positive control group (high cholesterol diet), high-cholesterol diet with Caulerpa sp. extract dose of 20 mg and 60 mg/100 g, high cholesterol diet with Gracilaria sp. extract dose of 20 mg and 60 mg/100 g body weight rat per day.The study resulted that rats fed high cholesterol diet with treated extract ethanol Caulerpa sp. and Gracilaria sp. with a dose of 20 mg and 60 mg per 100 g body weight rat / day had plasma MDA level significantly lower (p <0.05) compared with rats fed high cholesterol diet without treated with extract of Caulerpa sp. and Gracilaria sp.